Strategi Komunikasi Public Relation PPTN 4 Regional II Dalam Menjalankan Program Gerakan Cinta Produk PTPN - Nazlia, Tatia; Nasution, Nurhasanah (Universitas Muhammadiyah Sumatera Utara, 2025)
The importance of a brand in the development of product or service businesses is evident from the high consumer desire to use goods or services with well-known brands. A widely recognized brand is often associated with quality, trust, and certain values, which encourage consumers to choose it over other products or services. Based on the researcher’s observations, the problem that occurs is the high market competition in product sales. Therefore, with the